Clinical characteristics and prognosis of acute low-frequency hearing loss and ascending sensorineural sudden sensorineural hearing loss - Diao, Tongxiang; Chen, Yurun; Jing, Yuanyuan; Ma, Xin (Frontiers in Neuroscience, 2023)
Objective The present study aimed to explore the pathogenesis of the ascending sudden sensorineural hearing (SSNHL) loss by comparing the clinical characteristics and prognosis of acute low-frequency hearing loss (ALFHL) and ascending SSNHL. Methods A total of 43 patients with ALFHL and 122 patients with ascending SSNHL were enrolled in this study. First, the prognosis of patients with ALFHL and ascending SSNHL were compared, and the prognostic factors of AFHL and ascending SSNHL were analyzed. Results Acute low-frequency hearing loss and ascending SSNHL have no remarkable difference in complete recovery rate. Compared to ascending SSNHL, ALFHL has younger onset age, female prevalence, lower hearing threshold, shorter time from onset to recovery, and a lower proportion of combined tinnitus. The PTA at admission and delay from onset to therapy were significantly related to the prognosis of patients with ascending SSNHL, while only delay from onset to therapy was significantly related to the prognosis of patients with ALFHL. The majority of patients with ascending SSNHL and ALFHL recovered completely within 10 days from onset. Conclusion Audiogram shape plays a critical role in the prognosis of SSNHL. Ascending SSNHL and ALFHL may share a common pathological mechanism.